Ocular Syphilis in an Immunocompetent Young Man: Poster Presentation - Case Report - General practitioner - Vincentius Handy Suria; Halida Wibawaty (Majalah Oftalmologi Indonesia, 2023)
Introduction : Syphilis is called the great imitator because its clinical presentations vary widely and overlap with many other etiologies. We present a case of ocular syphilis in an immunocompetent young man with negative HIV test and history of unprotected sexual activities. Case Illustration : A 27 year-old male initially presented to an outpatient Solo Eye Hospital with complain of blurred vision and sudden visual impairment in the right eye and acute onset left eye redness, pain, clear discharge. His right eye VA was counting finger and 0,2 in his left eye. The patient diagnosed with acute posterior uveitis in the RE and acute iridocyclitis in the LE. A detailed sexual history, he endorsed having unprotected sex with numerous men in the past. Patient was subsequently started on P-Pred ED/2 hourly, atropine ED and testing to evaluate cause of iridocyclitis was sent. Fundus RE : clouded fundus view, vascular occlusion, vitreous opacification. Fundus LE : within normal limit. Rheumatoid factor negative, HIV antigen antibody screen non-reactive, syphilis IgG reactive, RPR screen reactive, RPR quantitative titer 1:128. ANA screen negative. The patient was started on intravenous penicillin G, and both his genital lesion and bilateral visual acuity improved. He was discharged to complete 14 fays of iv penicillin G. Discussion : HIV-positive patients may often present with ocular syphilis before the HIV status is known. Ocular syphilis is considered to be neurosyphilis for treatment purposes. Conclusion : Ocular syphilis should be kept in the differential diagnosis in immunocompetent/HIV negative patient, and the importance of obtaining a detailed sexual history should not be forgotten.